Colonization by benthic macroinvertebrates in two artificial substrate types of a Riparian Forest - Santos,Lívia Borges dos (2016)
Abstract: Aim To analyze the efficiency of organic and inorganic substrates in samples of benthic macroinvertebrates of riparian forests from the Cerrado. Specific objectives (i) characterize the ecological succession and taxonomic richness of benthic macroinvertebrates in stream affluent of a riparian forest; (ii) analyze the influence of seasonality on the colonization of macroinvertebrates; and (iii) determine the effect of the types of artificial substrates on the richness, composition and abundance of the benthic community. Methods Sampling was carried out in the rainy and dry seasons, and we installed in the watercourse two types of substrates: organic (leaf packs) and inorganic (bricks), organized in pairs. Six samples per season were done to verify colonization, succession, richness and abundance of benthic community. The substrates were carefully sorted and the organisms were identified to the lowest possible taxonomic level. Results The ecological succession was clearly observed, with the initial occurrence of Chironomidae and Baetidae (considered early colonizers), and a late occurrence of organisms such as Helotrephidae and Trichoptera (considered late colonizers). No significant difference was found in the richness and abundance among the studied seasons (rainy and dry), but the organic substrate was significantly higher than the inorganic substrate for these parameters. Conclusion Organic artificial substrates are more efficient in characterizing the community of benthic macroinvertebrates in the study area, because they are more similar to the conditions of the substrate found naturally in the environment.